Time‐dependent molecular fields created by the interaction of an external electromagnetic field with a molecular system. Issue 24 (15th July 2014) - Baer, Michael
<x xml:space="preserve">Abstract</x> When an external, time‐dependent field interacts with a molecular system various phenomena may take place. However, concentrating on a region close enough to a point of conical intersection, we find that this external field builds up a field similar to an electromagnetic field formed on the one hand by Field‐Dressed nonadiabatic coupling terms which are reminiscent of the Maxwell–Lorentz Vector potentials, and on the other hand via a scalar potential formed by the dipole‐interaction with an external field. In this article, we show that this new field, to be termed Molecular Field, is characterized by several spatial and space‐time Field‐Dressed Curl equations and one, single, space‐time Field‐Dressed Divergence equation. These equations are then shown to yield, just as in the general theory of electromagnetism, the corresponding Field‐Dressed Wave Equations. This achievement could be materialized employing the (1, 2) antisymmetric matrix elements of any of the 2×2 dimensional Field‐Dressed nonadiabatic coupling matrices. © 2014 Wiley Periodicals, Inc.